Mixed Mesonephric Adenocarcinoma and High-grade Neuroendocrine Carcinoma of the Uterine Cervix: Case Description of a Previously Unreported Entity With Insights Into Its Molecular Pathogenesis. (January 2017) - Cavalcanti, Marcela S.; Schultheis, Anne M.; Ho, Caleb; Wang, Lu; DeLair, Deborah F.; Weigelt, Britta; Gardner, Ginger; Lichtman, Stuart M.; Hameed, Meera; Park, Kay J.
Abstract : Human papillomavirus (HPV)-negative cervical carcinomas are uncommon and typically encompass unusual histologic subtypes. Mesonephric adenocarcinoma is one such subtype. Mesonephric tumors in the female genital tract are thought to arise from Wolffian remnants, and are extremely rare tumors with widely variable morphology. Sarcomatoid dedifferentiation has been previously described in a few cases, but other forms of dedifferentiation have not been reported. Neuroendocrine carcinoma of the cervix (e.g. small cell carcinoma) is associated with HPV infection, typically HPV 18. These tumors often arise in association with a conventional epithelial component such as squamous cell carcinoma or usual-type endocervical adenocarcinoma. We describe a case of mesonephric adenocarcinoma of the uterine cervix associated with an HPV-negative high-grade neuroendocrine carcinoma at the morphologic and immunophenotypic level, for which we performed targeted massively parallel sequencing analysis of the 2 elements. Both components shared identical mutations in U2AF1 p.R156H (c.467G>A) and GATA3 p.M422fs (c.1263dupG), as well as MYCN amplification. In addition, the neuroendocrine carcinoma harbored TP53 and MST1R mutations not present in the mesonephric carcinoma. Our data suggest a clonal origin of the 2 components of this rare entity, rather than a collision tumor. Abstract : Supplemental Digital Content is available in the text.